Pilote Annuel. (Dargaud, 1974)
Contiene historietas de los siguientes autores: Alexis; Dionnet y Tardi; Solé; Clavé; Massonnat; Mandryka; Bretécher; Cartry, Leconte; Colman Cohen; Grammat; Giraud; Lob; Pélaprat et Billón; Beketan; Jean Ache; Bilal; Gotlib; Leconte; Jijé; Freud.